Effect of Al concentration on the microstructural and mechanical properties of lightweight Ti60Alx(VCrNb)40-x medium-entropy alloys. (August 2021) - Liao, Y.C.; Ye, W.T.; Chen, P.S.; Tsai, P.H.; Jang, J.S.C.; Hsieh, K.C.; Chen, C.Y.; Huang, J.C.; Wu, H.J.; Lo, Y.C.; Huang, C.W.; Tsao, I.Y.
Abstract: Using the CALPHAD method, lightweight nonequiatomic Ti60 (Al)x (VCrNb)40-x (x = 6, 8, 10, 12, and 18 at.%) medium-entropy alloys (MEAs) were designed and produced using vacuum arc melting and drop casting. The density of these cast alloys decreased with an increase in Al concentration from 5.45 to 4.79 g cm −3 . All of these cast alloys exhibited a body-centered cubic (BCC) microstructure. However, a nanosized ordered B2 phase was identified in the cast alloys with higher Al concentrations (Al-12 and Al-18). The prediction of BCC phase formation using CALPHAD was consistent with the experimental results. These BCC-structured alloys can withstand over 50% strain at room temperature, which demonstrates excellent compressive ductility. Moreover, the results demonstrate that the as-cast Al-6 and Al-8 samples had superior plasticity under tensile testing, with a tensile strength of 1120 MPa and approximately 30% plastic strain. Furthermore, with an increase in Al concentration, the alloys exhibited a notable trend in yield strength and a decreasing trend in plastic strain. The change in mechanical properties of these MEAs caused by the formation of B2 nanoparticles was also investigated. Highlights: Novel alloys designing of lightweight medium-entropy alloys by calculation of phase diagrams. High strength with excellent ductility cast medium-entropy alloys. Fracture and strengthening mechanism was investigated in detailed.